2021
DOI: 10.1002/ptr.7198
|View full text |Cite
|
Sign up to set email alerts
|

Recent developments in the regulation of cholesterol transport by natural molecules

Abstract: The dysregulation of cholesterol metabolism is a high-risk factor for non-alcoholic fatty liver disease (NAFLD), dyslipidemia, and atherosclerosis (AS). Cholesterol transport maintains whole-body cholesterol homeostasis. Low-density apolipoprotein receptor (LDLR) mediates cholesterol uptake in cells and plays an important role in the primary route of circulatory cholesterol clearance in liver cells. Caveolins 1 is an integral membrane protein and shuttle between the cytoplasm and cell membrane. Caveolins 1 not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 62 publications
1
10
0
Order By: Relevance
“…Notably, the cholesterol biosynthetic process and metabolism pathways stood out in the proteomics and transcriptome data sets. As we know, cholesterol, a basic substance for life-sustaining activities [ 25 ], is not only important for the maintenance of blood circulation, including T-CHO and high-/low-density lipoprotein-cholesterol [ [26] , [27] , [28] ], but also the precursor of bile acid biosynthesis [ 29 ], which plays a key role in preventing the accumulation of toxic metabolites as well as violations of the liver and other organs [ 30 ]. The liver is the main organ of cholesterol synthesis which is represented by an intricate and multistep pathway [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the cholesterol biosynthetic process and metabolism pathways stood out in the proteomics and transcriptome data sets. As we know, cholesterol, a basic substance for life-sustaining activities [ 25 ], is not only important for the maintenance of blood circulation, including T-CHO and high-/low-density lipoprotein-cholesterol [ [26] , [27] , [28] ], but also the precursor of bile acid biosynthesis [ 29 ], which plays a key role in preventing the accumulation of toxic metabolites as well as violations of the liver and other organs [ 30 ]. The liver is the main organ of cholesterol synthesis which is represented by an intricate and multistep pathway [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cholesterol homeostasis is an important factor for liver health, and elevated liver cholesterol can induce hepatic steatosis [ 61 , 68 ]. Cholesterol is one of the basic components of cell membranes and is an essential precursor for the synthesis of bile acids and steroid hormones [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another important aspect of maintaining cholesterol dynamic balance is the transport of intracellular cholesterol. Excess cholesterol from the blood and endogenous cholesterol from food bind to lipoproteins and are transported into the liver as HDLs and CMs [ 47 , 68 ]. The levels of apolipoproteins (APOA and APOC) involved in these processes were significantly elevated in the hepatic steatosis group in this study, indicating an increase in exogenous cholesterol transport.…”
Section: Discussionmentioning
confidence: 99%
“…SCARB1 (scavenger receptor class B, type I) is a high-density lipoprotein (HDL) receptor that facilitates uptake of cholesterol (Cho) from HDL to hepatocytes [ 112 , 113 ]. Recently, it has been suggested that SCARB1 may be associated with NAFLD [ 114 ] and several studies suggest that fenofibrate affects SCARB1 [ 115 117 ]. Those studies have proposed that fenofibrate may enhance the degradation of SCARB1 in a postendoplasmic reticulum or postplasma membrane compartment [ 115 ].…”
Section: Discussionmentioning
confidence: 99%